Color Change Kinetics of Tea Leaves During Microwave Drying - Demirhan, Elcin; Ozbek, Belma (WALTER DE GRUYTER GMBH, 2015)
In the present study, the effect of microwave power and sample amount on color change kinetics of tea leaves was investigated during microwave drying. Hunter L, a and b system was used for the color change of the materials; and the total color change (Delta E), chroma, hue angle and browning index (BI) were calculated by using these values. The color of the tea leaves was shifted towards the darker region after themicrowave drying process. The mathematical modeling study of color change kinetic showed that a, b, chroma and BI fitted to a first-order kinetic model, while L, total color change (Delta E) and hue angle followed a zero-order kinetic model. For calculation of the activation energy for color change kinetic parameters, the exponential expression based on Arrhenius equation was used.
Keywords: microwave drying; tea leaves; color kinetic; activation energy; GRAPE JUICE; DEGRADATION; SPINACH; Food Science & Technology